Reading Genesis - Robinson, Marilynne (New York : Farrar, Straus and Giroux, 2024)
For generations, the book of Genesis has been treated by scholars as a collection of documents by various hands, expressing different factional interests, with borrowings from other ancient literatures that mark the text as derivative. In other words, academic question of its basic coherency, just as fundamentalist interpretation has centered on the question of the appropriateness of reading it as literally true. Both of these approaches preclude an appreciation of its greatness as literature, its rich articulation and exploration of themes that resonate through the whole of Scripture. Marilynne Robinson's Reading Genesis, which includes the full text of the King James Version of the book, is a powerful consideration of the profound meanings and promise of God's enduring covenant with humanity. This magisterial book radiates gratitude for the constancy and benevolence of God's abiding faith in creation.
Keywords: Bible.O.T. Genesis -- Criticism, interpretation, etc